Determining the Significance of Surface Roughness and Hardness Outputs of Grinding Cylinders Specifically for Laser Processing Parameters - Zekai Kivrim, Abdullah; Sahin, Omer Sinan; Ergun, Betul; Bagci, Mehmet (Journal of Composites and Biodegradable Polymers, 2025)
Surface roughness and hardness, critically important in industrial applications, are parameters that affect the performance and functionality of cast iron materials, particularly in various sectors. White cast iron is widely used in food milling due to its superior hardness and wear resistance. In parallel with all these advantages, grinding cylinders made of white cast iron wear to a certain extent due to the grinding of products such as wheat, barley, and coffee beans, necessitating periodic surface treatment. Laser processing has become widely used in recent years to modify the surface properties of metallic and composite materials. This experimentally significant study focused on investigating the effects of laser processing parameters on the surface roughness and hardness of grinding cylinders made of white cast iron. It was concluded that by using 10, 30 and 50 W, the desired hardness and roughness can be achieved by correctly selecting the process parameters. At the end of the experimental process, depending on the effect of power parameter variability, microscopic images showed a smooth surface texture, regional molten surface fluctuations and microcrater results in the presence of irregular solidification in the upper layer.